Caracterização química e biológica do óleo essencial das folhas de espécimes feminino e masculino de Baccharis punctulata DC - Oliveira, Murilo Silva de (2021)
Baccharis punctulata (Asteraceae) is a dioecious specie little studies chemically. This specie is use in Bustillo Province, Bolivia, in asthma, contusion and treatments, but there is no any work that supports your traditional use. The objective this work was to analyze the chemical composition of the essential oils from female (BPF) and male (BPM) of B. punctulata by Gaseous Chromatography coupled Mass Spectrometry and Flame Ionization Detector and to evaluate anti- inflammatory and antioxidant activities. The essential oils were extracted by hydrodistillation using medicated Clevenger apparatus. The anti-inflammatory activity was evaluated by through of inhibition of edema induced by 12-O-Tetradecanoylphorbol-13-acetate in ear mice inhibition of activity myeloperoxidase, reduction of reactive oxygen species and cell migration, the antioxidant activity was evaluated front DPPH radical. The majority compouds for BPF were bicyclogermacrene (42.44%), germacrene D (21.18%), β-caryophylene (14.06%) and limonene (3,40%) and for BPM δ-(14,29%),germacrene D (11,29%),icyclogermacrene (10,90%) e β-farnesene (6,74%). The isolate administration of TPA promoted a increase in MPO enzymatic activity and the inhibition of increase of MPO enzymatic activity for BPF was of 13.69 ± 0.20% 0.1 mg/ear), 22.35 ± 0.11% (0.3 mg/ ear) e 44.98 ± 0.27% (1.0 mg/ ear) while for BPM was of 22.40 ± 0.29% (0.1 mg/ear), 36.49 ± 0.07% (0.3 mg/ear) e 52.19 ± 0.28% (1.0 mg/ear).The dexamethasone positive control (0,1 mg/ear) was able to reverse the increase of MPO inzymaticctivity at in 65.16 ± 0.003. The istological analysis emonstrated that application of TPA promotes the call influx, however this inflammation was reduced with topical application of the samples BPF and BPM and of positive control. The results observed in ROS and DPPH assays show that both samples were able to reduce the inflammatory cells influx and have anti-inflammatory in vivo and antioxidant in vitro propriety. Was possible to conclude that the essential oils from female and male specimens of B. punctulata have chemical differences and have anti-inflammatory and antioxidant activity, supporting the use this specie in folk medicine.